2020
DOI: 10.3390/met10101385
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Cross-Shaped Structure of Invar Material Using Cold Wire Laser Fillet Welding (PART I: Feasibility Study for Weldability)

Abstract: With the need for eco-friendly energy increasing rapidly due to global environmental issues, there is a rapidly increasing demand for liquefied natural gas (LNG). LNG is liquefied at minus 163 degrees Celsius, and its volume decreases to 1/600, giving it a relatively higher storage and transport efficiency than gaseous natural gas (NG). The material for the tanks that store cryogenic LNG must be a material with high impact toughness at cryogenic temperatures. Invar, which contains 36% nickel and has a very low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Residual stresses were measured in white and grey cast irons after the cooling-down stage in thermal experiments [22]. There were several attempts to research the mechanism of thermal expansion in metals, focusing on white and grey cast irons [22], Invar [23], and copper-based amorphous alloys [24], as well as in ceramic-metal composites [25], but not enough information is available about CGI. Additionally, it was found that under multiple thermal cycles, the performance of cast iron was significantly influenced by longer-term thermal exposure [26].…”
Section: Introductionmentioning
confidence: 99%
“…Residual stresses were measured in white and grey cast irons after the cooling-down stage in thermal experiments [22]. There were several attempts to research the mechanism of thermal expansion in metals, focusing on white and grey cast irons [22], Invar [23], and copper-based amorphous alloys [24], as well as in ceramic-metal composites [25], but not enough information is available about CGI. Additionally, it was found that under multiple thermal cycles, the performance of cast iron was significantly influenced by longer-term thermal exposure [26].…”
Section: Introductionmentioning
confidence: 99%
“…Tayebi et al compared the mechanical properties after performing tungsten inert gas (TIG) welding and Nd:YAG laser welding tests for STS304L and STS316 materials [16]. Kim et al applied the cross-shaped structure of the Invar material to the LNG tank structure derived through the cold wire laser welding (CWLW) process [17]. Khan et al studied the alloying element loss and microstructure deformation of high-Mn austenitic stainless steels according to the type of laser welding, welding speed, laser power, and shielding gas flow rate [18].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al applied fiber laser welding using cold wire to a cross-shaped Invar of 1.5 mm and 3.0 mm thickness. By optimizing the welding conditions for the cross-shaped structure, which previously required 4 welding passes, the number of passes was reduced to 2 [21].…”
Section: Introductionmentioning
confidence: 99%